Histological evaluation of periapical tissue response after implantation of experimental nanostructured calcium aluminate cement: In vivo study - Radović Igor; Popović-Bajić Marijana; Bjelović Ljiljana; Erić Jelena; Lečić Jelena; Živković Slavoljub; Jokanović Vukoman (Serbian Medical Society - Dental Section, Belgrade, 2022)
Introduction ALBO-HA (Vinca, Serbia) is new nanostructured calcium aluminate cement, synthesized as a potential alternative to mineral trioxide aggregate (MTA). The purpose of this study was to compare the periapical tissue response to new nanostructured calcium aluminate cement ALBO-HA with white MTA (MTA Angelus, Londrina, Brasil) as root-filling material into the root canal of sheep' s teeth. Material and methods Sixteen mandibular incisors from two 24-month-old sheep were used. Root canals were pre pared and filled with ALBO-HA (group 1) or MTA (group 2) (eight teeth per group in each sheep). After four weeks the animals were sacrificed, teeth with surrounding tissue removed, and histologically processed. The sections were analyzed for determination of scores of the following parameters: periapical inflammatory infiltrate, newly mineralized apically formed tissue, apical periodontal ligament space thickness and resorption of dentin, cementum and bone. Data were analyzed statistically (a=0.05) using Mann-Whitney U test. Results Slight inflammatory infiltrate was observed in 75.0% and 62.5% of samples in the group 1 and group 2, respectively (p>0.05). Partial newly mineralized apically formed tissue was found in 75.0% of samples in the group 1, and 87.5% of samples in group 2 (p>0.05). No significant difference was noted for periodontal ligament space thickness (p>0.05). Resorption of dentin, cementum or bone was not observed. Conclusion ALBO-HA and white MTA Angelus had a similar effect on inflammation, newly mineralized apical tissue formation and thickness of periodontal ligament space after root canal filling under the present experimental conditions.